فرش القراءات القرآنية وتوجيهه بلاغيا : دراسة وصفية تحليلية في الأجزاء الثلاثة الأولى من القرآن الكريم - Syarifah Fatimah S. Abd Kadir (al-Jami'ah al-Islamiyah al-'Alamiyah bi Maliziya, 2009)
This study aims at examining a linguistic issue concerning the Qur'Én, that is the variant readings that are embodied in the orthoghraphy of the Qur'Énic text in terms of how to interpret them in the light of the science of rhetoric, which includes the explanation of the subtleties that lie there in. In order to achieve this objective, the descriptive and analytical approach is used for the investigation. In this respect, verses that embody the variant readings of orthoghraphic nature are sifted out from the first three segments of the Qur'Én and then categorized according to rhetorical classifications. The analysis is carried out based on explanations found in qirÉÒÉt and tafsÊr books. The study established that the variance in reading is meant to serve a some purpose and entails multiplicity of meanings which are not contradictory to each other. It was also established that since it is inconceivable that God's speech contain errors, inadvertant or otherwise, then the variance must be there for a reason. In the study, it is shown that through the variance, some messages are indirectly communicated such as God being wrathful toward the disbelievers and caring and considerate toward the Prophets and the believers. This is manifested in the analysis of the individual verses that have been subjected to treatment in this study.